Obstructed defaecation syndrome: European consensus guidelines on the surgical management - Picciariello, Arcangelo; O'Connell, P. R.; Hahnloser, D.; Gallo, Gaetano; Munoz-Duyos, A.; Schwandner, O.; Sileri, P.; Milito, G.; Riss, S.; Boccasanta, P. A.; Naldini, G.; Arroyo, A.; et al. (British Journal of Surgery, 2021)
Lay Summary Clinical decision-making in the treatment of patients with obstructed defaecation remains controversial and no international guidelines have been provided so far. This study reports a consensus among European opinion leaders on the management of obstructed defaecation in different possible clinical scenarios.
CRIS-Team WoS Importer:2021-11-26